(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: Pesticides cause short-term as well as long-term health effects. Agriculture workers are at high risk of effect. So, this study aimed to identify the health effects of pesticides among small-scale farmers in the municipality of Bhaktapur, Nepal. Methods: This was a community-based cross-sectional descriptive study conducted in all wards of Changunarayan Municipality, Bhaktapur, Nepal. Farmers of selected households who adopted agriculture as their main occupation were included in this study. The sample size for the study was 132. Proportionate stratified sampling was used to determine the farmer from each ward and simple random sampling was used to reach every respondent. Face-to-face interview technique and semi-structured questionnaire was used for data collection. The data were analyzed using descriptive statistics and the Chi-square test was applied to measure an association between selected variables. Results: All of the farmers used pesticides and about two-thirds 74(64.9%) experienced both immediate as well as delayed symptoms due to the use of pesticides. Majority of them showed general symptoms such as eye irritation 87(76.3%), difficulty in breathing 70(61.4%) and fatigue 55(48.2%). There was an association between the frequency of exposure and health effects due to pesticide use which was found to be statistically significant at a significance level with p-value 0.042. Conclusion: Health effects such as skin rashes, effects on the eyes, and respiratory system were reported. The most prevalent effects were eye irritation, difficulty in breathing, and itching of the skin. Training on pesticide use and awareness should be conducted by municipalities to reduce the effects.